Reading for understanding Methodist youths' shared Scripture- reading practices - Rackley, Eric D. (2018)
Informed by reading comprehension and comprehension strategies research, this study explores the Scripture-reading practices of four Methodist youths. Several rounds of inductive thematic analyses of Scripture-reading protocols revealed a set of five strategic reading practices youths used to understand Scripture. They drew inferences about the Bible's possible meanings, made connections between the Bible and other texts, made personal comments, recognized when they were confused, and applied prior knowledge. Identifying and naming these five strategic practices can deepen our understanding of the nature of Methodist youths' Scripture-reading practices and raise important questions about the relationships among youth, religion, and literacy.
Keywords: Comprehension; comprehension strategies; Literacy; Methodist; Reading; Religious Literacy